Preschool Environment and 24‐h Behaviour Movement in Uruguayan Early Childhood: A Compositional Data Analysis - Sofia Fernandez‐Gimenez; Clarice L. Martins; Enrique Pintos‐Toledo; Franco Souza‐Marabotto; Javier Brazo‐Sayavera (Child: Care, Health and Development, 2026)
ABSTRACT Background The preschool environment is a critical determinant of children movement behaviour; however, evidence integrating the 24‐h movement behaviour remains scarce, especially in the global south. Objective To identify the association between the preschool environment and 24‐h movement behaviour in Uruguayan preschoolers. Methods A cross‐sectional study was conducted with 112 preschoolers (45.32 ± 6.40 months) from Rivera, Uruguay. Movement behaviours were measured using accelerometry (Actigraph, wGT3X‐BT) and operationalized as a 24‐h composition. The preschool environment was audited in six domains: i) teacher role, ii) teacher training and education for family, iii) school policies, iv) indoor equipment, v) outdoor equipment, and vi) outdoor infrastructure. Multivariate linear regression models between preschool environment and isometric log‐ratio (ilr) coordinates of movement behaviours were conducted. Results The outdoor equipment environmental predictor significantly associated with the 24‐h movement behaviours composition (F = 3.40, p = 0.020), favouring the increase moderate‐to‐vigorous physical activity MVPA (β = 0.10, p = 0.027). Conclusions This research highlights Outdoor Equipment (availability, quantity and accessibility for preschoolers) as a key factor in promoting the movements behaviour and levelling the playing field for girls in moderate‐to‐vigorous physical activity.